A Comparison of Alfia Ibn Malek and Alfia Rabiee - Mahmood khorsandi; Haydar zohrab (دراسات في اللغة العربيّة وآدابها)
Â  Over the past years poems which elaborate on syntax have had a considerable role in teaching syntax so much so that some of these poems such asAlfiaby Ibn Malek has been studied as a basic text by students for several centuries. But in the modern time and due to the availability of moderntextbooks, these works have lost their significance. By studying the method of presenting syntax and inflections in two of these collection of didactic poems and comparing the two, this research intends to point out considerable positive and negative aspects in them and, accordingly, make some suggestions about the presentational style in didactic poems, the most important of which arethe logical and educationally sound sequence of syntactic and inflectional lessons, clarity of meaning, the use of correct poetic meter, the use of expressive and easy words, focusing on relevant scientific content.